(3GdeUHGM aj ENJUGQ GdeaJGMs - (3HOQ GdOjf eMeO Hf eMeO Hf YHO Gddg Hf eGdc GdOeTbjs; (3GdScGcj , SQGL GdOjf CHh jYbhH jhSa Hf CHj HcQ Hf eMeO Hf Ydj GdScGcj GdNhGQRej GdMfaj, GdScGcj,J (B626 (3g` s ((3EHQGgje Hf eMeO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG dgPG heG cfG fgJOi dhdG Cf gOGfG Gddg hSejJg cJGH GdeUHGM hLYdJg KdGKI CbSGe abdJ hHGddg GdJhajb GdHdGZI gi dHdhZ ai UhZ GdcdGe s
(3BNQgG (B:s
(3LedI deWdhH ai GdaGJMI hGdOYGA GdPi NJeJ Hg GdHbQI hGdhUGjG ai NGJeI Bd YeQGf hdjcf gPG BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdHdGZIs